Interactions of Alectinib with Human ATP-Binding Cassette Drug Efflux Transporters and Cytochrome P450 Biotransformation Enzymes: Effect on Pharmacokinetic Multidrug Resistance - Hofman, Jakub; Sorf, Ales; Vagiannis, Dimitrios; Sucha, Simona; Novotna, Eva; Kammerer, Sarah; Küpper, Jan-Heiner; Ceckova, Martina; Staud, Frantisek (Drug metabolism and disposition: the biological fate of chemicals, 2019)
Alectinib is a tyrosine kinase inhibitor currently used as a first-line treatment of anaplastic lymphoma kinase-positive metastatic nonsmall cell lung cancer (NSCLC). In the present work, we investigated possible interactions of this novel drug with ATP-binding cassette (ABC) drug efflux transporters and cytochrome P450 (P450) biotransformation enzymes that play significant roles in the phenomenon of multidrug resistance (MDR) of cancer cells as well as in pharmacokinetic drug-drug interactions. Using accumulation studies in Madin-Darby canine kidney subtype 2 (MDCKII) cells alectinib was identified as an inhibitor of ABCB1 and ABCG2 but not of ABCC1. In subsequent drug combination studies, we demonstrated the ability for alectinib to effectively overcome MDR in ABCB1- and ABCG2-overexpressing MDCKII and A431 cells. To describe the pharmacokinetic interaction profile of alectinib in a complete fashion, its possible inhibitory properties toward clinically relevant P450 enzymes (i.e., CYP1A2, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP3A4, or CYP3A5) were evaluated using human P450-expressing insect microsomes, revealing alectinib as a poor interactor. Advantageously for its use in pharmacotherapy, alectinib further exhibited negligible potential to cause any changes in expression of ABCB1, ABCG2, ABCC1, CYP1A2, CYP3A4, and CYP2B6 in intestine, liver, and NSCLC models. Our in vitro observations might serve as a valuable foundation for future in vivo studies that could support the rationale for our conclusions and possibly enable providing more efficient and safer therapy to many oncological patients.
Keywords: Madin Darby Canine Kidney Cells; systém (enzymů) cytochromů P-450; Protein Kinase Inhibitors; psi; ATP-Binding Cassette Transporters; Dogs; mnohočetná léková rezistence; Drug Resistance, Multiple; buňky MDCK; Cytochrome P-450 Enzyme System; biotransformace; chemorezistence; Biotransformation; Piperidines; Carbazoles; zvířata; Humans; Drug Resistance, Neoplasm; ABC transportéry; inhibitory proteinkinas; piperidiny; karbazoly; lidé; Animals